2011
DOI: 10.1074/jbc.m110.184317
|View full text |Cite
|
Sign up to set email alerts
|

Stable IgG-like Bispecific Antibodies Directed toward the Type I Insulin-like Growth Factor Receptor Demonstrate Enhanced Ligand Blockade and Anti-tumor Activity

Abstract: Bispecific antibodies (BsAbs) target multiple epitopes on the same molecular target or different targets. Although interest in BsAbs has persisted for decades, production of stable and active BsAbs has hindered their clinical evaluation. Here, we describe the production and characterization of tetravalent IgG-like BsAbs that combine the activities of allosteric and competitive inhibitors of the type-I insulin-like growth factor receptor (IGF-1R). The BsAbs, which were engineered for thermal stability, express … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 47 publications
(73 reference statements)
0
31
0
Order By: Relevance
“…The thermal stability profile of purified EI-04 as assessed by differential scanning calorimetry (DSC), shown in Figure 1D, confirms the T m of the stability-engineered BIIB5 scFv domain (~68°C) within the context of the final bispecific antibody format. 44 Stability studies of purified EI-04 BsAb showed the material to remain monomeric, homogeneous and stable at 4°C over at least 2 months at 25 and 50 mg/ml in a citrate-based pre-formulation buffer (data not shown).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 2 more Smart Citations
“…The thermal stability profile of purified EI-04 as assessed by differential scanning calorimetry (DSC), shown in Figure 1D, confirms the T m of the stability-engineered BIIB5 scFv domain (~68°C) within the context of the final bispecific antibody format. 44 Stability studies of purified EI-04 BsAb showed the material to remain monomeric, homogeneous and stable at 4°C over at least 2 months at 25 and 50 mg/ml in a citrate-based pre-formulation buffer (data not shown).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…C06 does not bind to rodent IGF-1R and the half-life of C06 was previously reported to be ~10 days in mice. 44 Therefore, M60-A02 and EI-04 were dosed twice weekly (BIW) to compensate for their faster clearance while C06 was dosed on a weekly schedule (QW) in the efficacy study.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…10 There are 3 broad categories of bispecific antibody design. The first category makes use of a conventional IgG [11][12][13] or Fab 14 as a platform, and introduces a second functional entity as a single variable domain (sVD), single-chain variable fragment (scFv) or single-chain Fab to the N-or C-terminus of the light chain (LC) or heavy chain (HC) via a flexible peptide linker, leading to tetravalent or hexavalent bispecific antibodies. Among the 3 formats, scFv is most popular because its compact structure of tandem linked V L and V H domains makes the molecule highly amenable to gene engineering, yet it still possesses complete antigen-binding activity.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering the stability of the antibody variable region has mainly focused on scFv due to its inherently poor stability. Stability of scFv can be improved by optimizing the hydrophobic core residues, charge cluster residues, residues which determine the framework subclasses, conserved proline and glycine residues, hydrophobic surface residues, and V H /V L interface residues using either a rational mutagenesis approach or a library approach [265,[318][319][320][321].…”
Section: Engineering To Improve Thermal Stabilitymentioning
confidence: 99%